The Potentials Of Palm Oil Plantation Wastes As Animal Feed At Traditional Farming In Teras Terunjam Subdistrict Muko-Muko District - Salam Aritonang; E. Roza; S. H. Tama (Jurnal Ilmu Ternak, 2018)
Research on the Potential of Palm Oil Plantation Waste as animal Feed at traditional farming in Teras Terunjam Sub District Mukomuko Regency aims to find out the potential of oil palm plantation wastes as animal feed as well as cattle maintenance pattern of beef cattle. The research method used is survey method by using questionnaire. The samples used were 61 farmer determined by Slovin formula. The observed variables are oil palm plantation waste potential as animal feed which consisted of the midrib and the leafs and technical aspects of livestock raisin. The data was analyzed descriptive based on score of Standard Guidelines Identification Technical Factor of Husbandry from Husbandry Directorate General (1990). The results showed that the potential waste of stem and midrib and the leafs from palm oil for the animal feed namely: 57.657.600 kg for each year and this also can feed 6.318,64 AU. As for the technical aspect in beef cattle farming in Teras Terunjam Subdsitrict, Muko-muko Regency namely: 54.31%, with categoris: 51.64% of breeding, 47.78% of feeding, 64.65% of maintenance, 89.25% of the housing, and 45.48% of healthy technical aspect.